2017
DOI: 10.1038/cddiscovery.2017.36
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear matrix metalloproteinases: functions resemble the evolution from the intracellular to the extracellular compartment

Abstract: Matrix metalloproteinase (MMP) is defined as an endopeptidase in the extracellular matrix (ECM), which plays essential roles in physiological processes such as organogenesis, wound healing, angiogenesis, apoptosis and motility. MMPs are produced and assembled in the cytoplasm as proenzymes with a cytoplasmic domain and require extracellular activation. MMPs can degrade receptors, extracellular matrix proteins, PARPs and release apoptotic substances. MMPs have been found in the cytosol, organelles and extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 58 publications
0
79
0
2
Order By: Relevance
“…This is conceivable because MT1-MMP harbors a putative nuclear localization sequence that may target the proteinase into the nucleus (23). Moreover, it has been suggested that MT1-MMP nuclear localization carries associated transcription-promoting activity (37). Accordingly, we evaluated by qPCR the mRNA levels (Table 2) for mt1-mmp, mmp-2, mmp-9, and, for App, bace-1 and the members of the g-secretase complex presenilin 1 (psen1), presenilin 2 (psen2), nicastrin (ncstn), presenilin enhancer 2 homolog (psenen) and aph1a, and for Abdegrading enzymes such as neprilysin (mme) and cathepsin D (CTSD).…”
Section: Mt1-mmp Activity Stimulates Production Of C-terminal C99 and Abmentioning
confidence: 99%
“…This is conceivable because MT1-MMP harbors a putative nuclear localization sequence that may target the proteinase into the nucleus (23). Moreover, it has been suggested that MT1-MMP nuclear localization carries associated transcription-promoting activity (37). Accordingly, we evaluated by qPCR the mRNA levels (Table 2) for mt1-mmp, mmp-2, mmp-9, and, for App, bace-1 and the members of the g-secretase complex presenilin 1 (psen1), presenilin 2 (psen2), nicastrin (ncstn), presenilin enhancer 2 homolog (psenen) and aph1a, and for Abdegrading enzymes such as neprilysin (mme) and cathepsin D (CTSD).…”
Section: Mt1-mmp Activity Stimulates Production Of C-terminal C99 and Abmentioning
confidence: 99%
“…The functions of nuclear MMPs are still poorly understood, although recent studies have explained some of them . No data are so far available regarding the functions of nuclear MMP2/9 in malignant mesothelioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has uncovered nontraditional roles for MMPs in the extracellular space as well as in the cytosol and nucleus . Several studies have shown that novel nuclear MMPs are associated with apoptosis . Increased nuclear gelatinolytic activity is associated with the processing of the DNA repair enzyme poly‐ADP‐ribose polymerase‐1 (PARP‐1), which protects cells from apoptosis and DNA fragmentation …”
Section: Introductionmentioning
confidence: 99%
“…Strong positive staining of the nucleus was observed in samples collected from the T2DM/GP group as compared to those from the control group. Nuclear localization of MMP7 has been associated with aggressive migration of cancer cells and decreased wound healing in cancer tissues . Although pathogenesis of cancer and periodontitis are not comparable, cell migration (pocket formation) and decreased wound healing are observed in patients with periodontitis with T2DM as well.…”
Section: Discussionmentioning
confidence: 99%